2010
DOI: 10.1007/s12028-010-9432-4
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Cerebral Interleukin-6 After Aneurysmal Subarachnoid Hemorrhage

Abstract: A pronounced initial cerebral inflammatory state was observed in patients of all WFNS grades, suggesting that IL-6 elevations are not necessarily detrimental. Cerebral, but not plasma IL-6, levels were predictive of the development of delayed ischemic deficits in symptomatic patients, suggesting that CSF or ECF are the best sampling media for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 37 publications
4
103
0
Order By: Relevance
“…In one sense, the degree of inflammatory responses could reflect the severity of EBI. Similar to our study, other studies also revealed that high levels of inflammatory cytokines such as IL-2, IL-6, IL-8 and CRP correlated with a higher clinical grade (4,9,11,17). The process of antiinflammation would be activated simultaneously after SAH,…”
Section: █ Resultssupporting
confidence: 89%
“…In one sense, the degree of inflammatory responses could reflect the severity of EBI. Similar to our study, other studies also revealed that high levels of inflammatory cytokines such as IL-2, IL-6, IL-8 and CRP correlated with a higher clinical grade (4,9,11,17). The process of antiinflammation would be activated simultaneously after SAH,…”
Section: █ Resultssupporting
confidence: 89%
“…Increased synthesis may be secondary to the host inflammatory response because the hemopexin promoter is interleukin-6 responsive, 11 and interleukin-6 levels are elevated in SAH CSF. 12 Decreased CD91-mediated scavenging may be because of plateauing in heme-hemopexin uptake because heme and hemopexin were detected simultaneously in the CSF. Also, because CD91 has multiple ligands, it is possible that there is competition for CD91 from other ligands, such as ApoE.…”
Section: March 2016mentioning
confidence: 99%
“…Some of the factors involved after ischemic stroke are tumor necrosis factor-a, interleukin-1b (IL-1b), IL-6, and inducible nitric oxide synthase, which are produced by a variety of activated cell types; endothelial cells, microglia, neurons, platelets, monocytes, macrophages, and fibroblasts (Huang et al, 2006). Furthermore, there is now clinical evidence of an upregulation of IL-6 after SAH (Sarrafzadeh et al, 2011).…”
Section: The Role Of Inflammation In Cerebrovascular Pathophysiology mentioning
confidence: 99%